Comparison of the environmental policies effectiveness under regimes of different political and economic structure, planned economy and economy in the process towards the free market: the case of Russia - Mavridakis F. (Selected readings on economies in transition, 2000)
The ecological problem appears to have been aggravated in the Soviet Union since the late 60's. Fifty years of Soviet dominance proved to be a sufficient period of time during which the consequences of the way the regime treated the environment first appeared. The purpose of this paper is to investigate the effectiveness of environmental policies under regimes of different political and economic structure, planned economy and economy in the process towards the free market. The analysis showed that environmental problems in the country today continue, in connection with the former regime, some of which may be worsened (e.g. radiation) because of the reduction of governmental subsidies. The regime changes had an effect on the handling of the problems.